Physical Medicine and Rehabilitation Management in Pediatric Patient with Postural (Positional) Clubfoot: A Case Report - Gloria Rondonuwu; Joudy Gessal; Patricia Kalangi (Universitas Sam Ratulangi, 2023)
Abstract: Clubfoot, talipes equinovarus, is a common term used to describe several kinds of ankle or foot deformities present at birth. This condition is one of the most treatable birth defects, often leading to normal or near-normal athletic activities later in life. We reported a patient with positional clubfoot treated with serial casting, passive manipulation, and stimulation. Male, 6 days old, lived in Sonder, with a chief complaint of right foot that bent inward since birth. Patient was consulted by pediatrician to physiatrist since the birth day. The bent inward foot was not accompanied by swelling and redness, and patient was seen calm when the foot being moved. Patient was treated by physiatrist with passive manipulation, four times weekly with serial casting, and everyday stimulation for feet. During treatment session, patient’s deformity was getting improved. After treatment, the deformity was corrected and patient’s foot was in normal position without any complication. The aim of medical rehabilitation of clubfoot was to reduce the deformity with the success criteria that foot could be functional, free of pain, good mobility, and did not require correction shoes, therefore, the patient could carry out normal activities after growing up. In conclusion, to produce the maximum correction results, good cooperation is required with the patient’s parents. Even though correction is optimal and done as soon as possible, if bone growth has not stopped, the clubfoot problem can reappear. The first element of management is correction of the cavus deformity by positioning the forefoot in proper alignment with the hindfoot. Keywords: postural clubfoot; physical medicine and rehabilitation; children; passive manipulation; serial casting; everyday stimulation for feet